2008
DOI: 10.1510/icvts.2008.193383
|View full text |Cite
|
Sign up to set email alerts
|

Worsened long-term outcomes and postoperative complications in octogenarians with lung cancer following mediastinal lymph-node dissection

Abstract: We evaluated the effects of mediastinal lymph-node dissection on outcomes in octogenarians with primary lung cancer. Outcomes and postoperative complications were retrospectively investigated in 48 octogenarians with anatomically resected lung cancer, of whom 23 underwent a mediastinal lymph-node dissection (ND2 group) and 25 a limited lymphadenectomy (ND0-1 group). Forty-three patients underwent a lobectomy, two a pneumonectomy, and three a segmentectomy. The five-year survival rate for all was 35%, while tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…According to some reports, radical mediastinal lymph node dissection in octogenarians resulted in increase of postoperative pulmonary complication, shorter survival, and increase of non-cancer related death. 14,18,19) More short and longterm results of pulmonary resection in octogenarians would need to be estimated.…”
Section: Discussionmentioning
confidence: 99%
“…According to some reports, radical mediastinal lymph node dissection in octogenarians resulted in increase of postoperative pulmonary complication, shorter survival, and increase of non-cancer related death. 14,18,19) More short and longterm results of pulmonary resection in octogenarians would need to be estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that pulmonary resection for elderly patients was a safe and feasible treatment for lung cancer, [2][3][4][5][6][7][8][9] especially in Japan ( Table 2). According to these reports, approximately 70% of patients were stage I.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that MLND is one of the main risk factors for postoperative complications. 5) On the other hand, we have previously reported the results of surgical treatment in octogenarians with lung cancer. 10) The morbidity was not significantly higher in the patients with lymph node dissection (ND1) than in those without lymph node dissection (ND0), including both hilar and mediastinal dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of post-operative complications in octogenarians was also investigated by Chida and colleagues. 29 Forty-eight patients were divided into two groups: those who received an anatomical lung resection and mediastinal lymphnode dissection (MLND group, n=23), and those who received an anatomical lung resection and regional (hilar) lymph node dissection and/or sampling (MLNS group, n=25). There was no significant difference in the rate of death from cancer extension during the observation period between the groups (MLND 52.3% vs MLNS 53.8%).…”
Section: Cost Of Extensive Mediastinal Dissectionmentioning
confidence: 99%